SMS Gateway as a Media to Improve Awareness and Dietary Compliance of Hypertensive Patients (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Hypertension is a major health problem in Indonesia. Prevention can be applied through health promotion and modification of a healthy lifestyle. The aim of this study was to analyze the effects of SMS (Short Message Service) Gateway to dietary compliance and awareness of hypertensive patients. The research design was pre-experimental with one group pretest-posttest design. The study was conducted at Putri Ayu Health Center, Jambi City. The sampling technique was accidental sampling with a total sample of 30 hypertensive patients. The intervention was conducted for 30 days by sending SMS twice a day. The results of the study showed an average awareness score of 7.3 pre-test and 10.1 post-test. The average dietary compliance score was 21.2 pre-test and 31.3 post-test. Wilcoxon test showed there was an effect of SMS Gateway to awareness and dietary compliance in hypertensive patients (p-value = 0.000). This study concludes that there is an effect of nutritional messages through SMS media to awareness and dietary compliance in hypertensive patients.